Nowhere Else - McCallum, Fiona (Australia Mira Books, 2011)
On the surface, current affairs reporter Nicola Harvey has the world at her feet. She is top of her profession, part of Australian television's celebrity A-list and has a wealthy and successful fiance. So when her boss sends her on a research trip to investigate the effects of the drought, she jumps at the chance.
Keywords: Man-woman relationships -- Australia -- Women journalists